PENGARUH KREATIVITAS SISWA DAN PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 PANGKALAN KERINCI - Saputri, Sari; Kartikowati, Sri; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to find out the effect of student' creativity and parents' attention to learning achievement. The research subjects were class XI IPS SMA Negeri 1 Pangkalan Kerinci with a total sample of 70 students. The research method uses purposive sampling. Data collection is done through technique questionnaires and documentation. Analysis of the data used is multiple linear regression supported by SPSS version 17.0 and calculations using manual formulas.The results of the study based on multiple linear regression showed that students' creativity and parents' attention had an effect on learning achievement on Economic subjects in class XI IPS in SMA Negeri 1 Pangkalan Kerinci, that can be seen from: (1) constanta value of 5,219, regression coefficient value of 0.241, and regresion coefficient of 0.351 with regression equation 5.219 + 0.241KS + 0.351PO, (2) calculation of R2 obtained value of 0.549. This means that the percentage contribution of student' creativity and parental attention to learning achievement is 54.9%. Based on these percentages in create for students it is recommended to further enhance students' creativity and to receive more their parents' attention, in order to improve more learning achievement.Key Words: Student' Creativity, Parents' Attention, Learning Achievement